The Grave Mound of a Saga Hero : A Case Study in Context and ‘Continuity’ between Grettis saga and Modern Folklore - Egeler, Matthias (Religionsvidenskabeligt tidsskrift, 2022)
ABSTRACT: The article presents a case study within the recent renaissance of folkloristic approaches to Old Norse-Icelandic religious history and saga literature. It undertakes a comparative analysis of medieval literary and recent local traditions about the burial of Ǫnundr Wooden-Foot, who was the great-grandfather of Grettir the Strong and an important character in the introductory chapters of Grettis saga. First, the article lays out the different accounts of Ǫnundr’s burial in medieval literature. Second, it contrasts the literary accounts with a broad range of more recent local traditions. Furthermore, it brings the physical topography of Ǫnundr’s alleged burial site into the discussion. The article then uses this ensemble of data to problematise issues such as the relative importance of chronological vs. geographical distance between a narrative and its alleged object, throwing new light on the relevance of recent local traditions for understanding medieval saga accounts.